2017
DOI: 10.1007/978-3-319-67262-5_1
|View full text |Cite
|
Sign up to set email alerts
|

On or Off the Blockchain? Insights on Off-Chaining Computation and Data

Abstract: The potential for blockchains to fundamentally transform how organizations produce and capture value is huge and very real. Practical applications dealing with nearly any type of digital asset demonstrate this capacity. Blockchain-based application architectures benefit from a set of unique properties including immutability and transparency of cryptographically-secured and peer-recorded transactions, which have been agreed upon by network consensus. Blockchain-based applications, however, may also suffer from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(105 citation statements)
references
References 4 publications
0
90
0
Order By: Relevance
“…Established off-chain mechanisms, like the Challenge-Response pattern mentioned by Eberhardt [9], may prove useful in stifling some of these attacks. One technique that deserves special mention at this point is sybil attacks.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Established off-chain mechanisms, like the Challenge-Response pattern mentioned by Eberhardt [9], may prove useful in stifling some of these attacks. One technique that deserves special mention at this point is sybil attacks.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…To circumvent these limitations, several mechanisms have been proposed in the past that allow processes to run off-chain while still relying on the Blockchain as the coordinator and final arbiter in case of dispute. Eberhardt and Tai [9] present an overview of common off-chain patterns. While their list was compiled from past experiences, we look towards a new set of problems with our approach that has not been tackled yet.…”
Section: Problem Motivation and Related Workmentioning
confidence: 99%
“…A common workaround suggested throughout the literature for aligning blockchains with the GDPR privacy requirements is the use of blockchains only for storing a timestamp and a hash that point to the actual information held off-chain [73], [74]. Therefore, when information needs to be amended or deleted only the fact that the specific content version existed Off-chain storage [73,74] Encrypted in blockchain…”
Section: A Bypassing Blockchain's Immutabilitymentioning
confidence: 99%
“…Bearing in mind that by using the stored hash alone the original content cannot be reconstructed, this workaround seems to resolve the blockchain's immutability collision with the RtbF rather elegantly. Indeed, off-chaining techniques so far are considered to be key tools in blockchain-based application engineering as they present significant benefits, such as reduced blockchain data storage requirements, and hence fewer scalability issues, and GDPR compliance [73], [55]. As a matter of fact, a recently conducted study [59] among experts concluded that blockchains could be indeed compliant with the privacy by design principles of the GDPR, and consequently with the RtbF, by employing these kind of off-chaining techniques.…”
Section: A Bypassing Blockchain's Immutabilitymentioning
confidence: 99%
“…Many flavours of approaches like weighted models [9], [10], [13], off-chain [14], [15], blockchain sharding [16]- [18] are proposed in recent researches to improve the performance of the blockchain. Many approaches attempt to ease the burden of individual nodes and solve the dilemma among having the ability to process everything, maintaining the decentralised system and increasing the performance.…”
Section: Introductionmentioning
confidence: 99%